2014
DOI: 10.1142/s0192415x14500207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Acupuncture for Carpal Tunnel Syndrome

Abstract: Acupuncture and electroacupuncture treatments of symptomatic carpal tunnel syndrome (CTS) may improve symptoms and aid nerve repair as well as improve sensory and motor functions. However, limited evidence is available regarding the effects of these treatments based on comprehensive evaluation methods. This research completed the treatment and evaluation of 26 patients with confirmed CTS. Participants were divided into two treatment groups based on a modified neurophysiological grading scale. Of the total numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
1
15
0
2
Order By: Relevance
“…After treatment, neurological function was improved by EA, consistent with the improved ultrastructural features of myelinated nerve fibers in EA groups. Given that myelin is important in normal nerve impulse conduction, the electronic stimulation may affect the electrophysiological conduction along axons [28][29][30].…”
Section: Promotion Of Oligodendrocyte Proliferation By Eamentioning
confidence: 99%
“…After treatment, neurological function was improved by EA, consistent with the improved ultrastructural features of myelinated nerve fibers in EA groups. Given that myelin is important in normal nerve impulse conduction, the electronic stimulation may affect the electrophysiological conduction along axons [28][29][30].…”
Section: Promotion Of Oligodendrocyte Proliferation By Eamentioning
confidence: 99%
“…Additionally, acupuncture has immune modulator and anti-inflammatory effects which might affect the inflammation in the entrapped median nerve in the carpal tunnel [19, 20]. In the previous literature, positive effects of acupuncture were shown in CTS patients [11, 12, 21]. Previously, in a randomized controlled study, acupuncture effects were compared with oral steroids in CTS patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Further, CSA of the median nerve at the wrist was a prognostic factor for carpal tunnel decompression surgery [9], and it might be used for monitoring of treatment [10]. In previous studies, acupuncture treatment has been shown as an effective and safe treatment modality for the CTS [11, 12]. However, to the best knowledge of the authors, the effect of the acupuncture on median nerve morphology has not been investigated in CTS patients before.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is a rehabilitation method in traditional Chinese medicine, through which the release of neurotrophic substances can be increased and promote nerve regeneration [11][12][13]. It was conducted as an adjuvant to electrical stimulation by therapists.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%